Education on Artificial Intelligence Utilization to Improve Employee Productivity at BUMDES Kamuning Jaya, Lebak Banten - Ichwan Putra Arianto; Anak Agung Gede Darma Jata; Santinah; Shelen Akmalia Retno; Faradila Nur Nopiyani (Majalah Ilmiah UPI YPTK, 2026)
The development of digital technology has significantly influenced various sectors, including village economic management through Village-Owned Enterprises (BUMDES). However, many BUMDES still face challenges related to limited human resources, administrative inefficiency, and low digital literacy. This community service activity aimed to provide education regarding the utilization of Artificial Intelligence (AI) technology to improve employee productivity at BUMDES Kamuning Jaya, Cikamunding Village, Cilograng District, Lebak Regency, Banten. The implementation methods included needs analysis, AI operational training, mentoring, and evaluation through pre-test and post-test assessments. The results showed a significant increase in participants’ understanding and skills regarding AI utilization, especially in prompt creation, information processing, administrative efficiency, and digital-based reporting. The average participant understanding increased from 50% in the pre-test to 73% in the post-test. This program demonstrates that AI-based education can improve employee productivity, support operational effectiveness, and strengthen village economic competitiveness through digital transformation. Keywords: Artificial Intelligence, Productivity, BUMDES, Digital Technology, Community Service